Performance of normal and nanomaterial Li(1+x)Mn2O4 for battery applications / Rozila Yusoff - Yusoff, Rozila (2010)
Stoichiometric of LiMn204 and none—stoichiometric of Li(1+x)Mn2O4 where (X: 0.1, 0.2, 0.3, 0.4 and 0.5) were prepared using the sol-gel method. Thermogravimetric Analysis (TGA) were done on the samples to study the thermal properties and decomposition of the precursors. The precursors were later heated for 72 hours at 850 °C. The annealed samples were characterized using X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FE-SEM) and Particle Size Analyzer. Fabrication of the cathodes and assembling of the batteries followed. The batteries were tested for their electrochemical chacteristics. Cyclic voltammetries were carried out using a three probe electrochemical cell. Materials with the best electrochemical chacteristics was chosen to prepared the nano material. The nano materials was prepared using high energy ball milling method using the Retsch PM 200. The nano samples were characterized using Field Emission Scanning Electron Microscope (FE—SEM), Transmission Electron Microscopy (TEM) and particle size analysis. Fabrication of the cathodes nano materials and assembling of the batteries were then carried out.